Modelling Antarctic lake ice responses to meteorological variables - Reid, Timothy Drummond (2005)
Inland Antarctic lakes are among the harshest environments in the world for life to inhabit. Ice cover causes low levels of light and temperature, and prevents mixing by wind, resulting in low nutrient levels and truncated food chains. Such ecosystems are widely regarded as sensitive indicators of climate change, and it is therefore useful to build up a strong physical and biological understanding of them. In 2003 an automatic probe (Palethorpe et al. 2004) was deployed on Crooked Lake, an ultra-oligotrophic freshwater lake in Eastern Antarctica which has been the subject of limnological studies since 1990. The probe measured several physical parameters in, above, and below the ice layer at temporal resolutions of up to one measurement every five minutes.